Pemahaman Legalitas dan Laporan Keuangan Usaha Mikro, Kecil, Menengah berdasarkan Standar Akuntansi Keuangan Entitas Mikro Kecil Menengah pada Pelaku Usaha Dagang - Febrianus sale, Blasius; Setiawan, Husein Tri; Sola, Silivanus (EDUPEDIA Publisher, 2023)
It is hoped that this service activity can support MSMEs in achieving good governance. In achieving good governance, MSMEs must have valid business legality and implement financial reports properly. This community service aims to provide understanding and strengthen the management of micro, small and medium enterprises (MSMEs) in terms of business legality and preparation of financial reports based on financial accounting standards for micro, small and medium entities (SAK EMKM). The method used in this PkM is presentation of material and training in the form of simulations and discussions. The material presented is legality and preparation of financial reports based on SAK EMKM. The PkM activity was carried out for one day on November 14 2023, with the activity participants being Toko Karya Sale which operates in the trading business sector. The results obtained from this activity are that MSME actors realize how important the legality of MSMEs is and MSME actors can know how to prepare MSME financial reports in accordance with the financial accounting standards for micro, small and medium entities (SAK EMKM).